Acute upper limb ischemia in a patient with COVID-19 (2020)
Patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection mainly present with upper and lower respiratory tract symptoms, with complications related to cytokine storm syndrome and acute respiratory distress syndrome. It has also been described to predispose to venous and arterial thromboembolism; however, limited published data is available regarding thrombosis in coronavirus disease 2019 (COVID-19). Here we are presenting a case of arterial thrombosis in a patient with COVID-19 and a systematic review on coagulopathy associated with COVID-19